Advantages of long-term combination pharmacotherapy with a beta-blocker and eplerenone in patients with ST-segment elevation acute coronary syndrome - O. A. Osipova; V. P. Mikhin; A. I. Golovin; O. N. Belousova; D. N. Perutsky; P. K. Alferov; S. L. Konstantinov (Кардиоваскулярная терапия и профилактика, 2022)
Aim. To conduct a comparative analysis of the effect of long-term pharmacotherapy (12 months) using a β-blocker (nebivolol) and its combination with eplerenone in patients after ST-segment elevation acute coronary syndrome (STE-ACS) with heart failure with mildly reduced ejection fraction (EF) (HFmrEF) on the structural and functional cardiac parameters.Material and methods. We examined 130 patients with STE-ACS and HFmrEF after successful myocardial revascularization by percutaneous coronary intervention. The mean age of patients was 53,6 [46;57] years. Ten patients withdrew from the study due to personal reasons. Subsequently, patients were randomly divided into 2 treatment groups as follows: 60 patients received nebivolol; 60 patients received nebivolol and eplerenone. Patients were examined at two stages: 1st day of the disease before PCI and 12 months later. All patients underwent a clinical examination, echocardiography, followed by assessment of left ventricular (LV) EF, LV end-diastolic volume index (EDVI), LV endsystolic volume index (ESVI), LV myocardial index (LVMI), LV wall motion score index (WMSI), the ratio of peak early diastolic flow over peak late diastolic flow (E/A), the ratio of early diastolic transmitral flow velocity to the mitral annular velocity (E/e´).Results. Twelve-month pharmacotherapy with nebivolol in patients after STE-ACS showed an increase in LVEF by 7,2% (p<0,05), a decrease in WMSI by 13,0% (p<0,05), an increase in the E/A ratio by 11,1% (р<0,05), decrease in the E/e’ ratio by 7,2% (р<0,05). LV EDVI increased by 4,6% (p>0,05). Twelve-month combined pharmacotherapy with nebivolol and eplerenone showed an increase in LVEF by 16,0% (p<0,01), a decrease in LV ESVI by 17,9% (p<0,05), and a decrease in WMSI by 26,7% (p<0,01), LVMI — by 23,8% (р<0,01). At the same time, LV EDVI decreased by 0,7% (p>0,05). The E/A ratio increased significantly by 22,2% (<0,01), E/e’ decreased by 29,6% (р<0,01). Comparative analysis also found that combination therapy had a more pronounced positive effect on LVEF (p<0,05), ESVI (p<0,05), WMSI (p<0,05), LVMI (p<0,01), as well as diastolic function in the form of a significant increase in E/A (p<0,05) and E/e’ (p<0,01), which recovered to normal values.Conclusion. The advantages of long-term combination pharmacotherapy of nebivolol and eplerenone in HFmrEF patients after STE-ACS on both structural and functional cardiac parameters were established.